2005
DOI: 10.1088/0953-8984/17/10/015
|View full text |Cite
|
Sign up to set email alerts
|

Electric transport and magnetic properties of perovskites LaMn1−xCoxO3up to 900 K

Abstract: The structural, magnetic and transport properties of the LaMn 1−x Co x O 3 system were investigated over a wide temperature range, 10-900 K. Two structural types, depending on x, were detected-orthorhombic Pbnm (x 0.5) and rhombohedral R 3c (x > 0.6), separated by the bi-phasic sample x = 0.6. At both ends of the LaMn 1−x Co x O 3 system, the respective substituents are unambiguously characterized as Co 2+ (x 0.1) and Mn 4+ (x 0.9). On the Mn-rich side, up to x < 0.5, we infer on the basis of high temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 41 publications
6
55
2
Order By: Relevance
“…Furthermore, BCu addition does not affect the high temperature limit of S of samples, all approaching $30 lV K À1 as T reaches around 500°C. The temperature behavior of S obtained here is basically consistent with previous studies for LaCoO 3 [25,26]. It was reported that S of doped LaCoO 3 could be estimated by the modified Heikes formula [27]:…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, BCu addition does not affect the high temperature limit of S of samples, all approaching $30 lV K À1 as T reaches around 500°C. The temperature behavior of S obtained here is basically consistent with previous studies for LaCoO 3 [25,26]. It was reported that S of doped LaCoO 3 could be estimated by the modified Heikes formula [27]:…”
Section: Resultssupporting
confidence: 92%
“…Further discussion is also raised by the work of Joy and coworkers, 21,22 who have synthesized two different single phases of LaMn 0.5 Co 0.5 O 3 and inferred from a combination of magnetic susceptibility and x-ray photoelectron spectroscopy measurements that the phase with the higher T C contains high- 11,26,27 Interesting is that the magnetization of polycrystalline samples of LaCo 0.5 Mn 0.5 O 3 does not saturate in magnetic fields up to 7 T, 16 and that there are indications for a large magnetic anisotropy.…”
mentioning
confidence: 99%
“…The effective backscattering amplitude F eff , the phase correction gðkÞ and the total central atom phase shift x were calculated for each scattering path with the FEFF8 program. The structural data obtained from X-ray diffraction measurements [1] served as the input parameters for calculations and the starting values for fitting. Total w function was constructed according to the equation:…”
Section: Discussionmentioning
confidence: 99%
“…The LaMn 1Àx Co x O 3 series exhibits a change of structure from orthorhombic, space group Pbnm, to rhombohedral, space group R-3c [1]. This change occurs around x ¼ 0:6 and is accompanied with a jump in the unit cell volume.…”
Section: Introductionmentioning
confidence: 99%